2006
DOI: 10.1103/physrevlett.97.206805
|View full text |Cite
|
Sign up to set email alerts
|

Transport Spectroscopy of a Single Dopant in a Gated Silicon Nanowire

Abstract: We report on spectroscopy of a single dopant atom in silicon by resonant tunneling between source and drain of a gated nanowire etched from silicon on insulator. The electronic states of this dopant isolated in the channel appear as resonances in the low temperature conductance at energies below the conduction band edge. We observe the two possible charge states successively occupied by spin-up and spin-down electrons under magnetic field. The first resonance is consistent with the binding energy of the neutra… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

21
287
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 264 publications
(309 citation statements)
references
References 18 publications
21
287
1
Order By: Relevance
“…As a consequence, the observation of quantum states in silicon nanowires requires very short channel lengths and there are only few reports of pronounced excited states in Si devices [9,10,11,12]. We have fabricated NiSi-Si-NiSi nanowires with a technique that allows the formation of dots shorter than 30 nm for which the stability diagrams of two representative devices are shown in the Supporting Information.…”
Section: Nov 2008mentioning
confidence: 99%
“…As a consequence, the observation of quantum states in silicon nanowires requires very short channel lengths and there are only few reports of pronounced excited states in Si devices [9,10,11,12]. We have fabricated NiSi-Si-NiSi nanowires with a technique that allows the formation of dots shorter than 30 nm for which the stability diagrams of two representative devices are shown in the Supporting Information.…”
Section: Nov 2008mentioning
confidence: 99%
“…In contrast to single atoms on metal surfaces, whose ground state is determined by the impuritysubstrate combination, transport experiments at different gate voltages can explore a wider parameter space. Signatures of single donors have been resolved and valuable information such as the electron-binding energy have been extracted [11][12][13][14] . Being a two-terminal device STM lacks a gate electrode for tuning the energy levels of nanostructures.…”
mentioning
confidence: 99%
“…In addition to the quantum size effect, which is commonly considered as the origin behind nanoscale phenomena [1], random dopant distribution has been reported as another source behind the changing in device performance [2][3][4]. More importantly, it has been reported that individual donor [5][6] and acceptor [7][8] may mediate carrier transport. This has opened an opportunity to utilize individual dopant as an active part for device functionalities.…”
Section: Introductionmentioning
confidence: 99%